Effect of flexural crack on plain concrete beam failure mechanism A numerical simulation - Abdoullah Namdar; Ershad Darvishi; Xiong Feng; Ideris Zakaria; Fadzil Mat Yahaya (Fracture and Structural Integrity)
The flexural failure of plain concrete beam occurs along with development of flexural crack on beam. In this paper by using ABAQUS, mechanism failure of plain concrete beam under three steps have been simulated. The cracking moment has been analytically calculated and applied on the both sides of the fixed beam, and flexural crack has been simulated on beam. Displacement, von Mises, load reaction, displacementcrack length, von Mises-crack length and von Mises-displacement of beams have been graphical depicted. Results indicated that, the flexural crack governs beam mechanism failure and its effects on beam resistance failure. It has been found that the flexural crack in initial stage it developed slowly and changes to be fast at the final stage of collapsing beam due to reduction of the flexural resistance of beam. Increasing mechanical properties of concrete, collapse displacement is reduced.